How do Laparoscopic and Open Surgical Approaches Compare in Terms of Post-Operative Complications, Recovery Time, and Quality of Life For Colorectal Cancer Patients? : A Systematic Review - Sean Gerry Santoso; Habel Ryan Annerico Sianipar; Freddy (International Medical Journal Corp. Ltd, 2026)
Introduction: Surgical resection is the primary curative treatment for colorectal cancer (CRC). While traditional open surgery has long been the standard, minimally invasive laparoscopic surgery has emerged as a widely used alternative. Its adoption is driven by potential short-term benefits, but a comprehensive understanding of its comparative impact on complications, recovery, and quality of life is essential for guiding clinical practice. This systematic review aims to synthesize and evaluate the evidence comparing laparoscopic and open surgical approaches for CRC. Methods: A systematic review was conducted adhering to PRISMA 2020 guidelines. Five electronic databases, including PubMed and Google Scholar, were searched for studies published since 2015 comparing laparoscopic versus open resection for CRC. The primary outcomes of interest were postoperative complications, recovery time, and quality of life. After screening thousands of records, 39 eligible studies, including randomized controlled trials and large meta-analyses, were included in the final qualitative and quantitative synthesis. Results: The analysis revealed that laparoscopic surgery was associated with significantly lower rates of overall postoperative complications in 23 of 26 reporting studies. Recovery was markedly faster with laparoscopy, with all 10 studies assessing hospital stay reporting shorter durations and a majority showing quicker return of bowel function. Long-term oncological outcomes, including survival and recurrence rates, were found to be equivalent between the two approaches in 12 of 16 studies. Data on quality of life were limited, with only one study reporting a short-term benefit for the laparoscopic group. Discussion: The consistent findings across multiple domains demonstrate a clear clinical advantage for the minimally invasive approach. The evidence strongly indicates that the short-term benefits of reduced patient morbidity and accelerated recovery do not compromise long-term oncological control, affirming the safety and efficacy of the laparoscopic technique. Conclusion: Laparoscopic surgery provides a superior short-term recovery profile and fewer complications than open surgery while offering equivalent long-term oncological safety. It should be considered the standard of care for most patients with colorectal cancer. Future research should prioritize investigating long-term, patient-reported quality of life to provide a more holistic comparison.